Evaluation of the effectiveness of an expressway sand protection system in a gobi region—case study of the Ceke–Ejina expressway, Ejina banner, China - Zhengyi Yao; Jianhua Xiao; Xixi Ma; Jianjun Qu; Xuefeng Hong (International Soil and Water Conservation Research)
Sand protection systems are widely used to shelter roads from blowing sand. Therefore, it's very important to evaluate their effectiveness. To provide some insights, we used field investigations, measurements of accumulated sand, work logs from sand-removal workers, and wind speed data to analyze a system's performance using China's Ceke–Ejina expressway as a case study. Our results demonstrated that the critical wind speed required to deposit sand on the expressway was 8.6 m s-1 (cumulative frequency 12.1%) before implementing the sand protection system. After implementing the system, the critical wind speed required to deposit sand on the road increased to 14.8 m s-1 (0.3%). However, the critical wind speed decreased to 11.1 m s-1 (3.5%) the next year. Additional work, such as digging ditches, increasing the fence height, and planting shrubs, would help the sand protection system retain its function. Nonetheless, the system continued to function well. The volume of sand removed decreased from ca. 10,000 m3 in 2015 to ca. 100 m3 in 2020. Our results quantify the effectiveness of the sand protection system and reveal how its effectiveness decreases over time. They therefore provide an empirical basis for improving the design and maintenance of sand protection systems.